2011
DOI: 10.1096/fj.11-181990
|View full text |Cite
|
Sign up to set email alerts
|

Dietary selenium affects host selenoproteome expression by influencing the gut microbiota

Abstract: Colonization of the gastrointestinal tract and composition of the microbiota may be influenced by components of the diet, including trace elements. To understand how selenium regulates the intestinal microflora, we used high-throughput sequencing to examine the composition of gut microbiota of mice maintained on selenium-deficient, selenium-sufficient, and selenium-enriched diets. The microbiota diversity increased as a result of selenium in the diet. Specific phylotypes showed differential effects of selenium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
174
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(187 citation statements)
references
References 27 publications
10
174
1
2
Order By: Relevance
“…Safdari-Rostamabad et al observed significantly greater jejunal villus height and crypt depth with 1.2 mg/kg nano-selenium supplementation in broiler chickens [30]. Dietary selenium affects both composition of the intestinal microflora and colonization of the gastrointestinal tract, which in turn influence the host selenium status and selenoproteome expression [32]. Harmful oxygen and nitrogen free radicals are produced during Se deficiency, while the antioxidant capacity in the intestine reduces, which together result in oxidative damage to chicken intestinal tissues [33].…”
Section: Discussionmentioning
confidence: 99%
“…Safdari-Rostamabad et al observed significantly greater jejunal villus height and crypt depth with 1.2 mg/kg nano-selenium supplementation in broiler chickens [30]. Dietary selenium affects both composition of the intestinal microflora and colonization of the gastrointestinal tract, which in turn influence the host selenium status and selenoproteome expression [32]. Harmful oxygen and nitrogen free radicals are produced during Se deficiency, while the antioxidant capacity in the intestine reduces, which together result in oxidative damage to chicken intestinal tissues [33].…”
Section: Discussionmentioning
confidence: 99%
“…Enteropathogenic E. coli (EPEC) and EHEC (e.g., E. coli O157:H7) are food-borne pathogens that are the causative agents for human diseases ranging from diarrhea to hemorrhagic colitis and hemolytic uremic syndrome. A recent study demonstrated an interesting effect of Se status on the composition of gut microbiota in mice (124). The diversity of intestinal microflora increased with increased Se intake, and there was potential competition between gut micobiota and the hosts for usage of available Se.…”
Section: Intestinal Inflammation and Food-borne Illnessesmentioning
confidence: 99%
“…Attempts to enhance gastrointestinal development and protect against infection and necrotizing enterocolitis have included use of prebiotics and probiotics, which bolster development of the microbiota. A recent study showed that although enteral supplementation with a prebiotic mixture of neutral and Protein calorie malnutrition, dietary deficiency (Moynahan, 1974;Stevens and Lubitz, 1998), high phytate (Moynahan, 1974;Stevens and Lubitz, 1998), transport deficiency (Moynahan, 1974;Stevens and Lubitz, 1998) Supplementation in infection (Stafford et al, 2013) Prenatal maternal supplement (Shah and Sachdev, 2006;Wieringa et al, 2010) Maternal supplementation (Terrin et al, 2013) Infant supplementation (Osendarp et al, 2007;Osendarp et al, 2006) Thymic atrophy, lymphopenia altered T-cell subsets, (Youn et al, 2008;Smith et al, 2008) Humans (Chen, 2012) HIV-1 infection (Shah and Sachdev, 2006;Wieringa et al, 2010;Smith et al, 2008) ↑Microbial diversity, composition, & colonization (Kasaikina et al, 2011) Required for glutathione peroxidase activity ↓NF-ÎșB activity, enhanced virulence of coxsackie B virus Deficiency in HIV-1 linked to progression, antiretroviral therapy increased levels acidic oligosaccharides did increase early postnatal intestinal colonization with a trend toward increased bifidobacteria, extensive use of broad-spectrum antibiotics counteracted the growth of all intestinal microbiota and delayed normal microbiota development (Westerbeek et al, 2013).…”
Section: Influence Of Nutrients In Priming and Development Of The Gasmentioning
confidence: 99%